2017
DOI: 10.4103/ijem.ijem_10_17
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine glands and hearing: Auditory manifestations of various endocrine and metabolic conditions

Abstract: The aetiology of hearing loss in humans is multifactorial. Besides genetic, environmental and infectious causes, several endocrine and metabolic abnormalities are associated with varying degrees of hearing impairment. The pattern of hearing loss may be conductive, sensori-neural or mixed. The neurophysiology of hearing as well as the anatomical structure of the auditory system may be influenced by changes in the hormonal and metabolic milieu. Optimal management of these conditions requires the integrated effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
3
0
5
Order By: Relevance
“…However, the above studies only included female participants and the luteinizing hormone, insulin, and other hormones could also influence their results [ 129 , 130 , 131 ]. In contrast, male patients with hypogonadism disorders such as Kallmann syndrome or Cogan syndrome were reported with sensorineural hearing loss but their hearing loss mostly has been attributed to genetic mutations rather than to testosterone deficiency only [ 132 ]. Although there is a lack of direct clinical evidence of testosterone and hearing loss, some studies considered that testosterone might have a negative impact on hearing because higher testosterone could lower the OAE amplitudes [ 66 ].…”
Section: How Could Hormones Influence Hearing In Molecular Aspects?mentioning
confidence: 99%
“…However, the above studies only included female participants and the luteinizing hormone, insulin, and other hormones could also influence their results [ 129 , 130 , 131 ]. In contrast, male patients with hypogonadism disorders such as Kallmann syndrome or Cogan syndrome were reported with sensorineural hearing loss but their hearing loss mostly has been attributed to genetic mutations rather than to testosterone deficiency only [ 132 ]. Although there is a lack of direct clinical evidence of testosterone and hearing loss, some studies considered that testosterone might have a negative impact on hearing because higher testosterone could lower the OAE amplitudes [ 66 ].…”
Section: How Could Hormones Influence Hearing In Molecular Aspects?mentioning
confidence: 99%
“…Molecular mechanisms that have been reported to contribute to hearing loss in XLH are depicted in Fig. 9, yet the aetiology of endocrinological and metabolic hearing loss is complex [229, 230], and the literature can be even more difficult to interpret than for other manifestations. As such, more work is needed to fully elucidate the molecular links between FGF23, XLH and hearing loss.
Fig.
…”
Section: Background and Introductionmentioning
confidence: 99%
“…Change of hippocampal structure is another potential procedure, by which sleep disturbed neural input from the central auditory system ( 11 , 13 ). Also, sleep curtailment strikingly altered metabolic and endocrine function, causing eustachian tube dysfunction and poorer nerve conduction ( 45 , 46 ). However, several other studies confirmed the association between short time of nocturnal sleep and HL ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%